The etiopathogenesis of atopic dermatitis: barrier disruption, immunological derangement, and pruritus - Pawinee Rerknimitr; Atsushi Otsuka; Chisa Nakashima; Kenji Kabashima (BMC, 2017)
Abstract Atopic dermatitis (AD) is a common chronic skin inflammatory disorder characterized by recurrent eczema accompanied by an intractable itch that leads to an impaired quality of life. Extensive recent studies have shed light on the multifaceted pathogenesis of the disease. The complex interplay among skin barrier deficiency, immunological derangement, and pruritus contributes to the development, progression, and chronicity of the disease. Abnormalities in filaggrin, other stratum corneum constituents, and tight junctions induce and/or promote skin inflammation. This inflammation, in turn, can further deteriorate the barrier function by downregulating a myriad of essential barrier-maintaining molecules. Pruritus in AD, which may be due to hyperinnervation of the epidermis, increases pruritogens, and central sensitization compromises the skin integrity and promotes inflammation. There are unmet needs in the treatment of AD. Based on the detailed evidence available to date, certain disease mechanisms can be chosen as treatment targets. Numerous clinical trials of biological agents are currently being conducted and are expected to provide treatments for patients suffering from AD in the future. This review summarizes the etiopathogenesis of the disease and provides a rationale for choosing the novel targeted therapy that will be available in the future.